PENGARUH PENDIDIKAN DAN PENGALAMAN KERJA TERHADAP KINERJA GURU MTS NEGERI 1 ENDE - Lasmi Niswatyi Zakiah; Rafael Oktavianus Byre (FAKULTAS EKONOMI UNIVERSITAS FLORES, 2021)
This study aims to determine the effect of: (1) Education on teacher work performance at MTs Negeri 1 Ende (2) Work experience on teacher work performance at MTs Negeri 1 Ende. This research includes causality research using a quantitative approach. The sample in this study were 35 teachers at MTs Negeri 1 Ende.. The data were collected using a questionnaire while the data analysis was carried out using multiple linear regression. The data were collected using a questionnaire that had been tested for validity and reliability.Multiple linear regression analysis was used to test the hypothesis of this study. The results of this study indicate that the level of education has a positive and significant influence on the work performance of MTs Negeri 1 Ende teachers and Work implementation has a positive and significant effect on the performance of MTs Negeri 1 Ende teachers.